Securitization of the Merchant Vessels by the Private Contracted Armed Security Personnel: A Legal Perspective - Selo Pasha Purnawarnantha; Arie Afriansyah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
Shipping trade commodities using commercial ships through the sea that are safe and free from security disturbances is a prerequisite for spinning a country's economy. However, not all seas in this world are safe. There are many areas of waters categorized as high-risk areas. UNCLOS regulates that a safe sea implies that the sea is free from threats or disruptions to the activities of peaceful sea use or utilization, among others, free from threats of violence in the form of piracy, sabotage, and armed terrorism at sea. Conditions gave rise to private security services on board called PCASP (Private Contracted Armed Security Personnel). This article aims to find out how to set up PCASP internationally and according to Indonesian law. This research uses secondary data materials, namely books, journal articles, and papers relevant to this research obtained from print and internet media. The use of PCASP supports the safety and security clause in UNCLOS 1982. IMO as an instrument of the United Nations in charge of maintaining and controlling international regulations on the safety and security of ships and ports. The maritime transportation authority in Indonesia does not require PCASP service nor approves commercial shipping companies to present PCASP on board.